Planned pregnancy affects primigravida readiness in role transitions - Sri Wahyuni; Aurelia Azharine Rasendrya; Yuni Sufyanti Arief; Mira Triharini (Journal of the Pakistan Medical Association, 2024)
Objective: To identify the correlation between planned pregnancy and role transition in primigravida. Method: The cross-sectional study was conducted at the Bandarharjo Health Centre, Semarang, Indonesia, from February to July 2022, and comprised married primigravida’s regardless of trimester who had never had a miscarriage. Data was collected using the London Measure of Unplanned Pregnancy, and the Body Understanding Measure for Pregnancy Scale instruments. Data was analysed using. the software SPSS version 26. P<0.05 was considered significant. Results: Of the 86 subjects, 40(46.5%) were aged 17-25 years, while 34(40.7%) were aged 12-16 years. All the 86 (100%) were married, although some of them acquired pregnancy before the wedding. There were 40(46.5%) unplanned pregnancies, and 36(41.9%) participants were ready for role change compared to 18(20.9%) who were not ready to face the new role. Planned pregnancy significantly correlated with primigravida readiness for role transitions (p=0.001). Conclusion: There was a significant relationship between planned pregnancy and readiness to face the role. Keywords: Pregnancy, Pregnancy, Unplanned, Family Planning, Abortion, Spontaneous.